2012
DOI: 10.3389/fncir.2012.00071
|View full text |Cite
|
Sign up to set email alerts
|

Sustained increase of spontaneous input and spike transfer in the CA3-CA1 pathway following long-term potentiation in vivo

Abstract: Long-term potentiation (LTP) is commonly used to study synaptic plasticity but the associated changes in the spontaneous activity of individual neurons or the computational properties of neural networks in vivo remain largely unclear. The multisynaptic origin of spontaneous spikes makes it difficult to estimate the impact of a particular potentiated input. Accordingly, we adopted an approach that isolates pathway-specific postsynaptic activity from raw local field potentials (LFPs) in the rat hippocampus in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…Applied to linear profiles of LFPs it can separate physiologically meaningful sources that can be attributed to known anatomical pathways, as has been demonstrated for the CA1, CA3 and dentate regions of the rat hippocampus (Benito et al, 2014; Fernandez-Ruiz et al, 2012a; Fernandez-Ruiz et al, 2012b; Fernandez-Ruiz et al, 2013). …”
Section: Star Methodsmentioning
confidence: 93%
“…Applied to linear profiles of LFPs it can separate physiologically meaningful sources that can be attributed to known anatomical pathways, as has been demonstrated for the CA1, CA3 and dentate regions of the rat hippocampus (Benito et al, 2014; Fernandez-Ruiz et al, 2012a; Fernandez-Ruiz et al, 2012b; Fernandez-Ruiz et al, 2013). …”
Section: Star Methodsmentioning
confidence: 93%
“…Enhanced mobilization of either pool could result in a decrease in presynaptic vesicles. Following induction of LTP, both evoked vesicle release probability (Enoki et al, 2009; Stanton et al, 2005; Zakharenko et al, 2001) and spontaneous miniature excitatory synaptic potentials (Malgaroli and Tsien, 1992; 1995; Manabe et al, 1992; Fernández-Ruiz et al, 2012) have been reported to be increased. Since the potentiation of the (evoked) fEPSP plateaued by 5 min, but TBS-related vesicle mobilization was only detected after 30 min, the persistent enhancement of vesicle mobilization seems more likely to have involved spontaneously released vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the size and geometry of the blocks of current represent the physical extension of the synchronously activated GCs, i.e., the portion of the GC population that elicits postsynaptic currents upon coherent activation of a group of axons from homologous afferent units (Benito et al, 2013). The FEM approach is widely used in magnetoencephalography and scalp electroencephalogram (EEG; Chen and Mogul, 2009;Salvador et al, 2011;Thielscher et al, 2011), although to the best of our knowledge it has not previously been used in the study of LFPs where the modeling approaches included realistic connectivity and/or membrane electrogenesis (Pauluis et al, 1999;Varona et al, 2000;Ló pez-Aguado et al, 2002;Lindén et al, 2011;Makarova et al, 2011;Ho et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, because the spatial coherence of LFPs may be due to macroscopic blending of nonoverlapping synaptic territories of functionally coupled neurons (e.g., interneuron networks), it is possible that statedependent modulation of network coupling disproportionately reduces the visualization of their associated LFPs with respect to individual firing rates, as demonstrated here by reducing the size of the activation strips. These observations are relevant to the study of the cellular mechanisms underlying LFP phenomena including dentate spikes, sharp waves, ripples, and field oscillations, which can appear at different hippocampal loci and with varying degrees of spatial coverage (Bragin et al, 1995a,b;Csicsvari et al, 2000;Bibbig et al, 2007;Reichinnek et al, 2010).…”
Section: The Spatial Heterogeneity Of Hilar Lfps Provides Insight Intmentioning
confidence: 99%